Italy : Financial Sector Assessment Program; Detailed Assessment of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses a Detailed Assessment of the Observance of the Insurance Core Principles for Italy. The assessment reveals that insurance supervision in Italy occurs within a legal framework that incorporates the relevant European Union Directives. More than two-thirds of the principles have been assessed as being observed or largely observed. Furthermore, the authorities in Italy are actively pursuing a number of legislative and supervisory initiatives that hold the potential to materially improve the level of observance in the near future.